Organizational socialization in the public service: on the actions and perceptions of newcomer and experienced employees - Reatto, Diogo; Brunstein, Janette (Revista de Administração da UFSM, 2020)
Purpose – This study aims to explain how the process of organizational socialization of newcomers occurs in a public faculty. Design/methodology/approach – This qualitative and interpretativist research was conducted under an interactionist approach. We interviewed 14 newcomers and also experienced government employees from a state public faculty in São Paulo. The content of the interviews was analyzed by a categorization process. Findings – The findings show that socialization of newcomers is self-motivated, informal, non-institutionalized, influenced by the normative nature of work and insufficient support given by the group. Newcomers’ admission into the workplace does not cause serious conflicts or tensions that could lead to changes in the workplace. It is the proactive behavior of the newcomers that allows them to adapt to work and know traditions, beliefs and history of the organization. Research limitations/implications – The limitation of this study is the context of a public university’s workplace. Practical implications – This research allows the organization to get information about the triangular relationship between challenge, support and trust which could have direct effects on the newcomers’ workplace learning. Social implications – We propose that the organization creates a workplace in which the employees can feel strong bonds of solidarity and collectivism, and in which they could have concrete opportunities to realize that their work can contribute to something important, impacting, in the group and in the organization. Originality/value – This study articulates the concepts of organizational socialization, proactive behavior and self-socialization, which may provide future implications for public management in universities.